Determinants of self-rated health of a working population - Marek Bryła; Monika Szymocha; Irena Maniecka-Bryła (Nofer Institute of Occupational Medicine, 2015)
Background: Self-rated health relates to the use of medical help and, as a consequence, determines sick leave in the population of employees. The aim of the study was to analyze the relationship between socioeconomic variables, selected forms of positive health behaviour and subjective evaluation of health in employees. Material and Methods: Five hundred and 99 subjects were included in the study - 331 females and 268 males, aged 18-67, working in the area of the Świętokrzyskie province. The authors' survey questionnaire on the selected elements of the state of health and positive health behavior in life style has been used in the study. Anthropometric measures were carried out. A Chi2 test for independence was used in the statistical analysis. In order to evaluate the effect of the selected factors on the self-rated health of the studied subjects the researchers have applied single- and multiple-factor logistic regression. Results: In the multiple-factor logistic regression the features contributing to good or excellent self-rated health were the following: age up to 39 (odds ratio - OR = 4.17; 95% confidence interval - CI: 1.72-10.10; p < 0.002), higher education (OR = 3.01; 95% CI: 1.04-8.70; p < 0.05) and care for health (OR = 4.77; 95% CI: 2.81-8.09; p < 0.001). Conclusions: Working people with higher education are characterized by a better control over their own health and, consequently, by a better perception of it. Monitoring self-rated health in a working population is an invaluable indicator in the evaluation of health in employees and the need for medical care. Med Pr 2015;66(1):17-28